A escadaria de terraços marinhos de Peniche (Portugal centro-oeste)-estratégias para a datação - Gouveia, Margarida (2019)
Summary:The Peniche staircase of marine terraces (central-west Portugal) dating strategies At the rocky coast of Peniche Peninsula, a staircase of six wave-cut surfaces and associated sedimentary deposits was identified. The strategies for the absolute dating of the several records of the Pliocene and Pleistocene marine incursions is here presented. The three lower marine terraces could be dated by optically stimulated luminescence, by using the proto-col pIRIR (k-feldspar as the dosimeter). The three upper terraces and the culminant marine unit could be dated by electron spin resonance. The limited thickness of the deposits does not allow the use of Cosmogenic (TNC) dating. The uppermost deposits of some of the marine terraces contain vertebrate bones and travertines, which could also be used for U-series dating (13) (PDF) A escadaria de terraços marinhos de Peniche (Portugal centro-oeste)-estratégias para a datação. Available from: https://www.researchgate.net/publication/327582780_A_escadaria_de_terracos_marinhos_de_Peniche_Portugal_centro-oeste-estrategias_para_a_datacao [accessed Feb 15 2019].